u2+3u-4=0

Consider the form x2+bx+c. Find a pair of integers whose product is c and whose sum is b. In this case, whose product is -4 and whose sum is 3.

-1,4

Write the factored form using these integers.

(u-1)(u+4)=0

(u-1)(u+4)=0

If any individual factor on the left side of the equation is equal to 0, the entire expression will be equal to 0.

u-1=0

u+4=0

Set the first factor equal to 0.

u-1=0

Add 1 to both sides of the equation.

u=1

u=1

Set the next factor equal to 0.

u+4=0

Subtract 4 from both sides of the equation.

u=-4

u=-4

The final solution is all the values that make (u-1)(u+4)=0 true.

u=1,-4

Solve using the Square Root Property u^2+3u-4=0